2007
DOI: 10.1007/bf03324708
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive stimulation intervention for elders with mild cognitive impairment compared with normal aged subjects: preliminary results

Abstract: Although further studies are needed for more details on the impact of cognitive stimulation programs on MCI patients, this intervention is effective in compensating associative memory difficulties of these patients. Among non-pharmacological interventions, cognitive stimulation therapy is a repeatable and inexpensive collective method that can easily be provided to various populations with the aim of slowing down the rate of decline in elderly persons with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 31 publications
4
60
0
12
Order By: Relevance
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%
“…Using multi-component cognitive training that included memory exercises, Kurz et al (2009) showed improved episodic memory measures in MCI individuals (California Verbal Learning Test and Rey Complex Figure Recall Test), as well as increases in daily living activities and mood. Furthermore, Wenisch et al (2007) showed that programs that included memory exercises resulted in an improvement of associative memory abilities in MCI and normal subjects (although a greater improvement was observed in MCI cases).…”
Section: Memory Interventions In Mild Cognitive Impairment and Alzheimentioning
confidence: 99%
“…The results showed that the cognitive ability of the two groups of people has significantly improved. The group of MCI patients has witnessed great improvements by the elderly people upon their ability of correlating memorization through cognitive intervention measures [4]. Belleville performed episodic memory training for MCI patients, including list recall, face-name memory strategies, and text memory.…”
Section: Introductionmentioning
confidence: 99%